Persistent Cough in Nonsmokers - Victor Hoffstein (Canadian Respiratory Journal)
OBJECTIVE: The purpose of this study was to test the hypothesis that, using Irwin's protocol, the majority of nonsmokers with persistent cough can be diagnosed and treated successfully.